AN ANALYSIS ON STUDENTS’ ERRORS IN PRONOUNCING ENGLISH WORDS - Andi Idayani (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The objective of this research is to know the students’ errors in pronouncing of English words on vowel and consonant sounds in the first semester of English students of FKIP UIR. The research design of this study is descriptive research. The researcher assessed the students’ errors pronunciation at English Language Education of FKIP UIR. The Respondent of this research was the first semester of English students of FKIP UIR. In this study, the research instrument is an oral test, there are 40 words that be tested, and the data was collected by a recorder. In analyzing the data, the researcher helped by other English lecturers as raters. Then, the data was checked by using talking-talking software and phonetic transcription. The result of this study described that there are some errors made by students in pronouncing English words. There are 25 students’ errors pronounced short vowel /e/, 15 students’ errors pronouncing short vowel /ᴜ/, 21 Students’ errors pronouncing the consonant / ð/, 18 students’ errors pronouncing consonant /ɵ/, and 17 students’ errors pronouncing consonant /ʒ/.